The Politics of Reforming Māori Education: The Transforming Potential of Kura Kaupapa Māori - Smith, Graham Hingangaroa (Towards Successful Schooling (RLE Edu L Sociology of Education), 1990)
The editors have compiled this critical and comparative study of changes which took place in the New Zealand education system in the second half of the twentieth century. For other Western societies who have felt the impact of New Right policies the New Zealand case is interesting because it provides some indication of how policies of decentralization in education might be used to develop egalitarian and democratic educational policies. In recent years there have been major changes to educational systems in the Western world. Often these changes have been justified by reference to successful educational practices in other countries. However, it is not always possible simply to abstract educational practices from one context and apply them in another successfully. Moreover claims that policies in one country are more successful than those in another have to be treated cautiously: there are always problems in making valid comparisons between the educational performances of different countries. It is important, therefore, that critical and comparative studies are made of educational systems which take full account of the contexts in which they are embedded.
Keywords: Education / Aims & Objectives; Education / General; Education / Philosophy, Theory & Social Aspects

The Political Economy of Inequality Between Maori and Pakeha - Poata-Smith, Evan Te Ahu (The Political economy of New Zealand, 1997)
Keywords: 1984-; Economic conditions; Economic policy; New Zealand; Politics and government

Realignment? Maori and the 1996 Election - Sullivan, Ann; Vowles, Jack (Voters' victory? : New Zealand's first election under proportional representation, 1998)
Keywords: New Zealand -- Politics and government -- 1984-; New Zealand -- Politics and government -- 1996-; New Zealand Parliament -- Elections, 1996; Proportional representation -- New Zealand

Modern Māori: the Young Māori Party to Mana Motuhake - Sorrenson, M. P. K. (The Oxford illustrated history of New Zealand, 1990)
Keywords: History; New Zealand

Mana wahine theory: Creating space for Māori women’s theories - Pihama, Leonie (Mana wahine reader: A collection of writings, 1999)

Not Ceded but Redistributed - Williams, Joe (Sovereignty & indigenous rights: the Treaty of Waitangi in international contexts, 1991)
Keywords: government relations; kāwanatanga; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; tāngata whenua

Race Relations and the Treaty: A Framework for Resolution - Gardiner, Wira (Partnership and peace: essays on biculturalism in Aotearoa - New Zealand, 1990)
Keywords: government; race relations; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Development: Sovereignty or Dependency? - Henare, Manuka (Puna wairere: essays, 1990)
Keywords: development; ethnic identity; inequity; partnership; rangatiratanga; social conditions

Maori Claims: Is the Challenge Being Met? - Durie, Edward (Puna wairere: essays, 1990)
Keywords: ethnic identity; social conditions; tiriti o waitangi/treaty of waitangi; treaty claims; treaty settlements

Whaia te iti Kahurangi: Maori women reclaiming autonomy - Kupenga, Vapi; Rata, Rina; Nepe, Tuki (Puna wairere: essays, 1990)
Keywords: ethnic identity; mana wāhine; social conditions; social status

Back to the future: Maori Survival in the 1990s - Williams, Joe (Puna wairere: essays, 1990)
Keywords: colonisation; ethnic identity; social conditions; tiriti o waitangi/treaty of waitangi

Chapter 6: Iwi Development and the Waikato-Tainui Experience - Mahuta, Robert (Nga Patai: racism and ethnic relations in Aotearoa/New Zealand, 1996)
Keywords: development; iwi; iwi development; race relations; racism; rangatiratanga

The Treaty and the word: the colonization of Māori philosophy - Jackson, Moana (Justice, ethics and New Zealand society, 1992)
Keywords: environment; kaupapa māori; philosophy; print only; rangatiratanga; social justice; sovereignty; tiriti o waitangi/treaty of waitangi

Land Loss and the Treaty of Waitangi - Jackson, Moana (Te Ao Marama: Regaining Aotearoa: Maori Writers Speak Out: Volume 2: He Whakaatanga o te Ao: The Reality, 1993)
Keywords: can't find source - further research required

Chapter 5: He Pōkeke Uenuku i Tu Ai: The Evolution of Contemporary Māori Protest - Poata-Smith, Evan (Nga Patai : Racism and Ethnic Relations in Aotearoa New Zealand, 1996)
The evolution of contemporary indigenous protest in Aotearoa/New Zealand.
Keywords: activism; mana motuhake; protest; rangatiratanga